1956
DOI: 10.1146/annurev.bi.25.070156.000533
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Lipides

Abstract: Since the chemistry of the lipides was reviewed by Hilditch (1) in 1953, new and interesting fatty acids have been discovered and the mechanisms of autoxidation and of fat -synthesis have become better understood, as has the relationship between fatty acid composition and species. In this review it -is proposed to emphasise items selected from publications that have become available during the year ending November, 1955.FATTY ACIDS Estimation and separation.-As a means of separating fatty acid mixtures paper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1956
1956
1970
1970

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Based on the optical rotations of relevant fractions as compared with the purified acids (cf. Shorland et al 1955) the percentages of anteiso-acids were calculated as C15, 0-11, and C17, 0-18 %. No reliable estimate of the i8o-acids could be made, but from the amounts isolated it appears that they are present in proportions similar to those of the anteiso-acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the optical rotations of relevant fractions as compared with the purified acids (cf. Shorland et al 1955) the percentages of anteiso-acids were calculated as C15, 0-11, and C17, 0-18 %. No reliable estimate of the i8o-acids could be made, but from the amounts isolated it appears that they are present in proportions similar to those of the anteiso-acids.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants the odd-numbered i8o-and anteisoacids in the depot and milk fats were considered by El-Shazly (1952) to be formed by the addition of acetate units to isovaleric and (+ )-2-methylbutyric acid derived from leucine and isoleucine by the action of bacteria in the rumen. Shorland et al (1955) have suggested that the normal oddnumbered fatty acids might similarly arise from propionic and valeric acids present in the rumen. The origin of the odd-numbered normal, isoand anteiso-acids of shark-liver oil cannot at present be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anteiso acids were allowed for in calculating the fatty acid compositions. i8oand n-Odd-numbered acids have been found in cow-milk (Shorland, 1956) but, as there is no DISCUSSION satisfactory analytical technique for determining the percentages present, they have not been recorded in the As shown in Table 2, the New Zealand and English present work. (Hilditch & Jasperson, 1944) ewe-milk fats are…”
Section: Methodsmentioning
confidence: 70%